2019
DOI: 10.1186/s12866-019-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

The proteolytic activity of Listeria monocytogenes HtrA

Abstract: BackgroundHigh temperature requirement A (HtrA) is a widely expressed chaperone and serine protease in bacteria. HtrA proteases assemble and hydrolyze misfolded proteins to enhance bacterial survival under stress conditions. Listeria monocytogenes (L. monocytogenes) is a foodborne pathogen that induces listeriosis in humans. In previous studies, it was shown that deletion of htrA in the genome of L. monocytogenes increased the susceptibility to cellular stress and attenuated virulence. However, expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Meanwhile, their chaperon activity might facilitate the repair of damaged DNA or altered DNA and RNA structures arising in osmotic stress exposed L. monocytogenes cells. The two-component regulatory system LisRK and the chaperone and serine protease high-temperature requirement A (HtrA) are known to play roles in osmosensing, osmoregulation, and osmotolerance in L. monocytogenes [ 21 , 78 ]. Csps might also exert their influences through these systems.…”
Section: Role Of Csps In L Monocytogenes Stress Tolerancementioning
confidence: 99%
“…Meanwhile, their chaperon activity might facilitate the repair of damaged DNA or altered DNA and RNA structures arising in osmotic stress exposed L. monocytogenes cells. The two-component regulatory system LisRK and the chaperone and serine protease high-temperature requirement A (HtrA) are known to play roles in osmosensing, osmoregulation, and osmotolerance in L. monocytogenes [ 21 , 78 ]. Csps might also exert their influences through these systems.…”
Section: Role Of Csps In L Monocytogenes Stress Tolerancementioning
confidence: 99%
“…Moreover, a similar study on a different Gram-positive pathogen, Staphylococcus aureus , showed that it is required for motility and growth at high temperatures (Savijoki et al, 2020 ). Lmo0292 protein, also known as “high temperature requirement A” (HtrA), acts as a chaperone and serine protease (Abfalter et al, 2019 ). ClpP and Lmo0292 were present in all conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in order to optimize the binding kinetics and functional activity, a more potent H. pylori HtrA inhibitor (Table 1, compound 4) is discovered by computer-assisted de novo molecular design [64]. Even more surprising is that the activity of L. monocytogenes HtrA can also be effectively blocked by compound 4, which suggests the broad-spectrum applicability of this compound [65]. In addition, JO146 (Boc-Val-Pro-ValP (OPh) 2) (Table 1) is screened by targeting the in vitro protease activity of Chlamydia trachomatis HtrA, which completely prevent the formation of viable Chlamydia elementary bodies when used during the replicative phase of development Fig.…”
Section: The Pros and Cons Of Exploiting Htra Inhibitors In Antibacterial Drug Developmentmentioning
confidence: 99%